Tailor made ionic liquids: catalyst and media for organic transformations - Chandra, Prakash; Shinde, Sandip S.; Biradar, Ankush V. (Current Organic Chemistry, 2015)
Ionic liquids are considered as one of the safe, green and environmentally benign solvents/catalysts for many organic reactions. Particularly, imidazolium based ionic liquids attracted much attention in basic as well as applied research. The major role of these ionic liquids is the replacement of the existing corrosive solvents, which are largely used in most of the organic processes and make these processes more eco-friendly. Recent report reveals the importance of imidazolium based ionic liquids, supported on silica gel or polystyrene in catalysis. The solid supports have well versed properties such as easy anchoring of ionic liquid, chemically and mechanically very stable and inert in nature. These ionic liquids can be tailored either by covalent attachment or simple deposition of the ionic liquid on the surface of the support. Both approaches showed enhanced reactivity and selectivity for various reactions. In this review, we made an attempt to review the recent reports related to synthesis and applications of tailor made ionic liquids and their use as catalyst in Aldol, Friedel-Crafts alkylation, hydroformylation, nucleophilic substitution and biomass transformation reactions.
Keywords: Green solvent; heterogeneous catalyst; organic transformation; sustainable process; task-specific ionic liquids